2009
DOI: 10.1017/s1355617709991019
|View full text |Cite
|
Sign up to set email alerts
|

Differential engagement of cognitive and affective neural systems in pediatric bipolar disorder and attention deficit hyperactivity disorder

Abstract: This fMRI study investigates the neural bases of cognitive control of emotion processing in pediatric bipolar disorder (PBD) and attention deficit hyperactivity disorder (ADHD). Seventeen un-medicated PBD patients, 15 un-medicated ADHD patients, and 14 healthy controls (HC) (mean age = 13.78 ± 2.47) performed an emotional valence Stroop Task, requiring them to match the color of an emotionally valenced word to the color of either of two adjacent circles. Both patient groups responded significantly slower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
104
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 64 publications
23
104
3
5
Order By: Relevance
“…The absence of a group difference in emotional-specific interference is in line with some studies (Passarotti et al, 2010a(Passarotti et al, , 2010b but does not correspond to others where emotional interference has been shown when individuals with ADHD were performing EF tasks (Köchel et al, 2014;López-Martín et al, 2013;Marx et al, 2011;Posner et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The absence of a group difference in emotional-specific interference is in line with some studies (Passarotti et al, 2010a(Passarotti et al, , 2010b but does not correspond to others where emotional interference has been shown when individuals with ADHD were performing EF tasks (Köchel et al, 2014;López-Martín et al, 2013;Marx et al, 2011;Posner et al, 2011).…”
Section: Discussionsupporting
confidence: 69%
“…Fifth, more importantly, ADHD is a clinically and etiologically heterogeneous disorder and therefore the current findings may not generalize to the ADHD population as a whole or to other ADHD samples. Finally, to exclude the possibility that at the behavioral level no deficit was apparent because of compensatory strategies (Passarotti et al, 2010a), studies may need to adopt neuroimaging measures (e.g., electroencephalography, functional Magnetic Resonance Imaging).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when positive stimuli are used, ADHD subjects show hyperactivation in these regions (91). Similarly, two independent studies using the emotional Stroop task found hypoactivation in ADHD in right medial and ventrolateral prefrontal cortex while processing negative distractors but hyperactivation in left medial prefrontal cortex while processing positive distractors (92,108). Such work represents the first stage in charting the neural basis of dysregulated attentional control in ADHD in the presence of emotional stimuli.…”
Section: Section 2: Pathophysiologymentioning
confidence: 64%
“…Children with PBD show overactivity in a ventral affective system, consisting of the amygdala, striatum, paralimbic cortex, and subgenual anterior cingulate cortex (ACC) while processing emotional stimuli, such as faces Pavuluri et al, 2007;Rich et al, 2006), scenes (Chang et al, 2004), or words (Passarotti et al, 2010a;. Patients with PBD also show variable activity in ventrolateral prefrontal cortex (VLPFC) areas linked to emotional regulation while completing a variety of affective tasks (Blumberg et al, 2003;Passarotti et al, 2009Passarotti et al, , 2010aPavuluri et al, 2007Pavuluri et al, , 2009b. In a recent pharmacological fMRI study, patients asked to remember emotional faces showed normalized VLPFC activity and reduced, but still elevated, amygdala overactivity after 14 weeks of lamotrigine monotherapy, suggesting partial prefrontal functional recovery with persistent limbic dysfunction .…”
Section: Introductionmentioning
confidence: 99%